Feasibility Analysis of Namicalung Village to Become Majalaya's Legendary Sarong Weaving Tourism Village - Shinta Larista; Rheinanda Awliya Agista; Dewa Alit Dwija Putra (CV. Syntax Corporation Indonesia, 2024)
Woven textiles, a vital aspect of Indonesia's cultural heritage, greatly influence the Nusantara archipelago's identity. Majalaya in West Java, known as the